2001
DOI: 10.2337/diabetes.50.12.2652
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Regulation of Mitochondrial and Cytoplasmic Protein Synthesis Rates by Insulin

Abstract: In vivo studies have reported conflicting effects of insulin on mixed tissue protein synthesis rates. To test the hypothesis that insulin has differential effects on synthesis rates of various protein fractions in different organs, we infused miniature swine (n ‫؍‬ 8 per group) with saline, insulin alone (at 0.7 mU/kg ؊1 ⅐ min ؊1 ), or insulin plus an amino acid mixture for 8 h. Fractional synthesis rate (FSR) of mitochondrial and cytoplasmic proteins in liver, heart, and skeletal muscle, as well as myosin hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
75
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 60 publications
4
75
0
1
Order By: Relevance
“…Previous studies have meticulously revealed many of the subcellular mechanisms by which insulin stimulates muscle protein synthesis, most involving the up-regulation of translational steps (39,40). However, Boirie et al (11) showed that this up-regulation may not be a global effect on all proteins, but that specific protein pools (i.e., mitochondrial proteins) may be targeted. It may be that specific proteins having greater numbers of mRNA Insulin concentrations sustained during 7 h of insulin infusion (mean Ϯ SD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have meticulously revealed many of the subcellular mechanisms by which insulin stimulates muscle protein synthesis, most involving the up-regulation of translational steps (39,40). However, Boirie et al (11) showed that this up-regulation may not be a global effect on all proteins, but that specific protein pools (i.e., mitochondrial proteins) may be targeted. It may be that specific proteins having greater numbers of mRNA Insulin concentrations sustained during 7 h of insulin infusion (mean Ϯ SD).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ratio between oxidative and glycolytic enzyme activities is decreased in skeletal muscle from type 2 diabetic subjects compared with nondiabetic subjects (6). A recent report by Boirie et al (11) on miniature swine has also demonstrated that insulin infusion preferentially stimulates the fractional synthesis rate (FSR) of skeletal muscle mitochondrial proteins. In contrast, 2 wk of insulin treatment did not stimulate muscle mitochondrial protein synthesis and cytochrome c oxidase (COX) activity in people with type 2 diabetes mellitus (DM) (12).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…A reduced mitochondrial protein synthesis rate (as occurs in aging) (26) may contribute to muscle weakness and decrease in VO 2max . Insulin has been shown to stimulate muscle mitochondrial protein synthesis in a swine model (27). In this study, we also investigated whether muscle mitochondrial, sarcoplasmic, and mixed muscle protein synthesis are altered in people with type 2 diabetes.…”
mentioning
confidence: 99%
“…L'insulina è anche il maggiore regolatore delle proteine muscolari e può stimolare la sintesi delle proteine mitocondriali [63], e un danno della funzione mitocondriale può promuovere IR negli uomini [64]. L'IR è associata a un range di fattori di rischio cardiovascolare che include dislipidemia, ipertensione, intolleranza al glucosio e diabete [65].…”
Section: Danno Cardiopolmonare Nella Pcosunclassified